In silico approach of antiviral compound from Cymbopongon citratus as the main protease SARS-CoV-2 inhibitor - Steven Arianto (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2025)
A pandemic known as COVID-19 is brought on by the RNA virus SARS-CoV-2. SARS-CoV-2 has some protease enzymes, such as main proteases (Mpro), that regulate the expression of viral non-structural proteins. The Mpro protein is a possible target for SARS-CoV-2 antiviral therapy because the inhibition of Mpro will disrupt the virus replication process and stop the virus life cycle. Lemongrass is an Indonesian spice with bioactive compounds whose benefits have not been widely explored, especially as an antiviral for SARS-CoV-2. This study aimed to identify potential bioactive chemicals in lemongrass that have antiviral properties for treating COVID-19. This methodology research began by preparing the bioactive compounds of lemongrass and Mpro protein. Using Lipinski’s rule of five, the nine bioactive chemicals found in lemongrass were examined to see how similar they were as therapeutic compounds. Next, PyRx 0.8 (Virtual Screening Tool) and PyMOL were used to perform molecular docking and its interaction with the Mpro protein. Diethyl phthalate has antiviral and anti-inflammatory activity with low binding energy (-5.8 kcal/mol) for Mpro and is stably bound (RMSF < 3Å) via hydrophobic bonds (His41, Met165) and hydrogen bonds (Phe140, His163, His164, Glu166, Gln189). It is concluded that diethyl phthalate on lemongrass demonstrated high promise as an inhibitor of SARS-CoV-2 viral replication based on the findings of the comprehensive investigation of these bioactive chemicals.